449 C〉G polymorphism of NFKB1 gene,coding nuclear factor-kappa-B,is associated with the susceptibility to ulcerative colitis - Hayashi, Ranji (World journal of gastroenterology : WJG, 2012)
AIM：To clarify the association between a polymorphism-449 C〉G（rs72696119） in 5＇-UTR of NFKB1 with ulcerative colitis（UC）.METHODS：The studied population comprised 639 subjects,including patients with UC（UC cases,n = 174） and subjects without UC（controls,n = 465）.We employed polymerase chain reaction-single strand conformation polymorphism to detect the gene polymorphism.RESULTS：The rs72696119 G allele frequencies in controls and UC cases were 33.4% and 38.5%,respectively（P = 0.10）.Genotype frequency of the GG homozygote in UC cases was significantly higher than that in controls（P = 0.017）,and the GG homozygote was significantly associated with susceptibility to UC [odds ratio（OR）,1.88;95%CI,1.13-3.14].In male subjects,the GG homozygote was associated with an increased risk for UC（OR,3.10;95%CI,1.47-6.54;P = 0.0053）,whereas this association was not found in female subjects.In addition,the GG homozygote was significantly associated with the risk of non-continuous disease（OR,2.06;95%CI,1.12-3.79;P = 0.029）,not having total colitis（OR,2.40;95%CI,1.09-3.80,P = 0.040）,disease which developed before 20 years of age（OR,2.80;95%CI,1.07-7.32,P = 0.041）,no hospitalization（OR,2.28;95%CI,1.29-4.05;P = 0.0090） and with a maximum of 8 or less on the UCDAI score（OR,2.45;95%CI,1.23-4.93;P = 0.022）.CONCLUSION：Our results provide evidence that NFKB1 polymorphism rs72696119 was significantly associated with the development of UC.This polymorphism influences the susceptibility to and pathophysiological features of UC.